Object and goals of developmental psychology - Vilches S., Liliana (Revista de Psicología, 1991)
In its more general attention, Developmental Psychology can be defined as the study of the changes and transformations that human beings experience throughout the vital cycle of their existence in their psychic and organic aspect. However, in a particular way it corresponds to the knowledge of the inevitable and normal modifications that occur in individuals, as they grow and increase in age, in the different areas of their psyche. In addition to involving the study of physical and neurological changes. Facts that constitute the biological substratum of the evolution of psychic life, Developmental Psychology is devoted to a great extent to the knowledge of the ways of presenting psychomotor, intellectual, affective-emotional and social development.